Testing predictions from self determination theory using Programme for International Student Assessment (PISA) 2012 data for mathematics learning - Böyüksolak, Arif. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
The main aim of the study was to test the predictions of SDT in the sample of PISA 2012 for mathematics learning domain. In this study, data for SDT related variables were obtained from the data supplied by PISA 2012 study. Mathematics autonomy, mathematics competence and relatedness to school were expected to predict mathematics intrinsic and extrinsic motivations signi cantly and positively in the total sample of PISA 2012 (N= 485490). The relationships between variables were transformed in to SEM. Moreover, cultural invariance of the e ects of the basic psychological needs on types of mathematics motivation was tested in the nine countries (Finland, Japan, Lithuania, Russia, Thailand, Spain, UK, Turkey, and Brazil) which were selected from nine di erent cultural clusters in WVM 6 (N= 93659). MG-CFA and MG-SEM were used to test the cultural invariance.The proposed model t the data in the total sample of PISA 2012. Except for the relationships between relatedness to school and mathematics intrinsic motivation, all of the relationships between basic psychological needs and types of mathematics motivation were signi cant. Although there is a di erences in the signi cance of the relationships of relatedness to school for Thailand and Spain with respect to other countries, the di erence were not statistically signi cant and an empirical evidence for the cultural invariance of the effects of basic psychological needs was provided by the results. As a result, except for the relationship between mathematics intrinsic motivation and relatedness to school, all of the predictions of SDT were consistent with the results obtained by this study.
Keywords: Mathematical ability -- Testing.